2019
DOI: 10.1103/physrevc.99.025204
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon axial form factor from a Bayesian neural-network analysis of neutrino-scattering data

Abstract: The Bayesian approach for feed-forward neural networks has been applied to the extraction of the nucleon axial form factor from the neutrino-deuteron scattering data measured by the Argonne National Laboratory bubble chamber experiment. This framework allows to perform a modelindependent determination of the axial form factor from data. When the low 0.05 < Q 2 < 0.10 GeV 2 data are included in the analysis, the resulting axial radius disagrees with available determinations. Furthermore, a large sensitivity to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…The height of the F A local maximum is reduced once the deuteron correction is included; this maximum disappears when the first bin has been removed from the ANL data. The value of r A for the best fit corresponds to the BIN2 data and has a value compatible with other determinations such as the z-expansion ones from bubble chamber data [9] and from muon capture by protons [10] but with a significantly smaller error [1]. We realize that deuteron effects are sizable by looking at the changes in the behavior of F A at low Q 2 when we add the deuteron corrections and when we take out the first bins of the data.…”
Section: Numerical Results and Summarysupporting
confidence: 76%
See 1 more Smart Citation
“…The height of the F A local maximum is reduced once the deuteron correction is included; this maximum disappears when the first bin has been removed from the ANL data. The value of r A for the best fit corresponds to the BIN2 data and has a value compatible with other determinations such as the z-expansion ones from bubble chamber data [9] and from muon capture by protons [10] but with a significantly smaller error [1]. We realize that deuteron effects are sizable by looking at the changes in the behavior of F A at low Q 2 when we add the deuteron corrections and when we take out the first bins of the data.…”
Section: Numerical Results and Summarysupporting
confidence: 76%
“…
We have performed the first Bayesian neural-network analysis of neutrino-deuteron scattering data [1]. The nucleon axial form factor has been extracted from quasielastic scattering data collected by the Argonne National Laboratory (ANL) bubble chamber experiment using a modelindependent parametrization.
…”
mentioning
confidence: 99%
“…(12) has only a single free parameter, M A , which should be fixed by fitting the experimental data. It should be also noted that, in the Breit frame and for small momenta, such Q 2 dependence of AFF leads to an exponentially decrease for the axial charge distribution [55]. However, from a theoretical point of view, it has been indicated that this ansatz is not a good choice, e.g.…”
Section: Experimental Datamentioning
confidence: 99%
“…In particular, the authors of Ref. [55] have used this tool to analyze the neutrino-deuteron scattering data measured by the Argonne National Laboratory (ANL) bubble chamber experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In a non relativistic approach, the dipole distribution is the Fourier transform of an exponential charge distribution. Other models and parametrizations are available (axial-Vector dominance [22], neural-network Bayesian analyses [23]) as well as recent results from lattice QCD [24]. In this letter the axial form factor is calculated in frame of Vector Meson Dominance (VDM).…”
Section: A the Nucleon Axial Form Factormentioning
confidence: 99%